MANAJEMEN KEUANGAN SYARIAH: PERAN SAKINAH FINANCE - Eny Latifah; Rudi Abdullah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The aim of this research is to determine sharia financial management in the sakinah finance model which includes: Income Management, Needs Management, Dream/Desire Management, Surplus/Deficit Management, and Contingency Management in fulfilling sharia maqashid. The research method used is descriptive with a library approach. The results of the research are sharuag financial management using the sakinah finance model in meeting daily needs through family financial management which is dominated by mothers. The role of sakinah finance in fulfilling maqoshid sharia for society can be seen from: (1) as a controller of household expenditure including: education, health, investment and Zakat Infaq Sadaqoh (2) As an evaluation in managing family finances to avoid waste and extravagance. (3) As a good and careful financial planner in meeting the needs of family members.